Increasing The Influence of Polymers in Lithium Batteries - Fahmi Yekti Waluyo; Markus Diantoro; Fahmi Yekti Waluyo; Markus Diantoro (Universitas Negeri Malang, 2026)
Recently, there has been much innovation in the energy storage system. The famous energy storage system now is Lithium battery, due to high energy density, little capacitance lost, and efficiency. But in the way of explosion, extreme temperature, liability to explode again, and precipitate lithium that didn't evenly become bad for lithium batteries. Actually now there is much research innovation to enhance lithium batteries performance. Mostly in modification materials like synthesis, doped, and composite. And in another way, polymers also turn out to be material batteries. In 1970 some scientists discovered an innovative polymer for battery material. It's an open new view in science knowledge, especially material development of batteries. Therefore these research polymers in lithium batteries material to increase. To responses of enhancement performance of lithium batteries material, we make comparison between polymer usage and non-polymer usage (synthesis, doped, composite) for lithium batteries. The result from non-polymer usage showed composite had highest specific capacity(1349 mAh.g-1), but doped also had high specific capacity even though not more than composite methods. On the other hand, the use of polymers showed the highest specific capacity of 2237 mAh.g-1. However, the use of non-polymers was far superior, providing higher average specific capacity values. Therefore, the use of common materials modified through synthesis, doping, and composites remains the best way to improve the performance of lithium batteries today.